False-Positive 18F-FDG PET/CT Imaging: Dramatic "Flare Response" After Rituximab Administration. (March 2016) - Skoura, Evangelia; Ardeshna, Kirit; Halsey, Richard; Wan, Simon; Kayani, Irfan
Abstract : Abstract: We report the case of a 45-year-old woman diagnosed with non-Hodgkin lymphoma. Six months after completion of R-CHOP, she relapsed, and 2 cycles of R-ESHAP were given, with a view to allograft transplant. One month later, 18 F-FDG PET/CT revealed disease progression. Biopsy of lymph nodes showed reactive changes, without evidence of lymphoma. Rituximab, a monoclonal antibody, is used for treatment of non-Hodgkin lymphoma, but its addition may result in an extensive inflammatory response. It is important to be aware of the potential for false-positive 18 F-FDG PET/CT imaging after rituximab therapy. Unexpected findings should be confirmed by biopsy.